Generalized anxiety disorder among mothers attending perinatal services during COVID-19 pandemic: using ordinal logistic regression model. Issue 6 (June 2022) - Lelisho, Mesfin Esayas; Merera, Amanuel Mengistu; Tareke, Seid Ali; Hassen, Sali Suleman; Jemal, Sebwedin Surur; Markos kontuab, Admasu; Bambo, Meseret Mesfin
Abstract: Background: Generalized anxiety disorder is characterized by excessive and uncontrollable worry about a variety of events. It is critical to ensure a pregnant mother's mental health in order to reduce pregnancy and birth-related problems. The major goal of current study was to identify the factors associated with generalized anxiety disorder among mothers attending perinatal services in the study area during COVID-19 using ordinal logistic regression. Methods: The institution-based cross-sectional study was conducted from July 10 th, 2020 to August 10 th, 2020 at Kembata Tembaro zone, Southern Ethiopia. The current study included 423 mothers. The GAD-7 scale was used to assess the anxiety level among mothers. An Ordered logit model was used to identify the determinants of GAD. Brant test of the parallel line was utilized to check proportionality assumption. The statistical significance was determined using an adjusted proportional odd ratio with a 95%CI, and a p-value <5%. STATA software version 14 was used to analyze statistical data. Results: Of all 423 mothers attending perinatal service during COVID-19; 134(31.7%), 171(40.4%), 85(20.1%), and 33 (7.8%) had non/minimal to severe generalized anxiety disorder respectively. The results of multivariable proportional odds model (POM) showed that the variables town residents [aPOR = 1.827; 95% CI:1.233–2.708], having alcohol habit [aPOR = 3.437, 95% CI = 1.397–8.454], having occupation [aPOR = 0.509, 95% CI: 0.303–0.857], being health care worker [aPOR = 0.117, 95% CI = 0.044–0.311], having chronic illness [aPOR = 7.685, 95% CI = 3.045–19.39], having family history of anxiety/mood disorder [aPOR = 7.839, 95% CI = 2.656–23.12], fear of contracting COVID-19 [aPOR = 1.704, 95% CI = 1.152–2.521], having moderate social support [aPOR = 0.648, 95% CI = 0.425–0.989], having strong social support [aPOR = 0.495, 95% CI = 0.272–0.901] were significantly associated with generalized anxiety disorder at 5% level of significance. Conclusion: Current findings concluded that the prevalence of GAD among mothers attending perinatal service during COVID-19 was high. The covariates like being town resident, lower-income status, occupation status, having a chronic illness, having a positive family history of anxiety or mood disorder, perceived social support, and fear of the COVID-19 were significantly associated with generalized anxiety disorder among mothers. Mothers who visit perinatal services should be given special consideration to improve health care services and ensure their mental health. Abstract : Generalized anxiety disorder; Mental health; Prenatal period; COVID-19.